PERAN MAHASISWA AKUNTANSI SEBAGAI PENDORONG USAHA MIKRO KECIL MENENGAH BERSAING DALAM ERA MASYARAKAT EKONOMI ASEAN - Tri Rani Putri, Desak Nyoman; Anggya Agustina, Putu Ayu (E-Jurnal Akuntansi, 2017)
ASEAN Economic Community (AEC) is a community that has direction to built an integrated economic region by reducing trade transaction costs, fixing trade and business facilities also improving competitiveness Micro Small Medium Entreprises (MSME) sector. Indonesia is a part of AEC has a large quantity of MSME sector but not followed by equal quality. MSME, especially micro and small scale has some barriers in a few issues, one of them is minimum access to finance because of accountancy lack comprehension in recording business transaction. To do a solving model needs role of accountant and accountancy. Student of accounting as a part of it will show their roles in Accounting Students’ modified “KKN” that will become a massive action, step by step and continue to force SMSE to be able to compete in AEC through every step that suitable to Accounting Standard as appointed.
Keywords: AEC, SMSE, Accounting Students’ role, KKN